Characteristics of HOTS Oriented Learning at the Elementary School Level - Maspupah, Isti Aulia (Universitas Sebelas Maret, 2020)
Teachers are always required to always update the changes that occur, so that learning is able to prepare students to face the changes that occur. One of the important things that can be done by teachers is to develop HOTS-oriented learning so that students become accustomed to critical thinking so that they are able to develop their creativity. The purpose of this study is to determine the concept of higher order thinking skills, aspects of higher order thinking skills, HOTS-oriented learning characteristics. The results of this study are: Higher order thinking skills are thinking skills that are not just remembering, restating, and also referring without processing, but thinking skills to examine information critically, creatively, and able to solve problems, Skill-oriented learning higher order thinking is learning that involves 3 (three) aspects of higher order thinking skills, namely: transfer of knowledge, critical and creative thinking, and problem solving. The characteristics of HOTS-oriented learning must make students active in thinking.